Atomic dispersion monatomic catalyst and preparation method and application thereof
By doping metal elements in nanocluster intermediates, the problems of poor stability and reactivity of 2e-ORR catalysts are solved, efficient and sustainable hydrogen peroxide production is achieved, and traditional Energy consumption and waste problems of H2O2 production methods.
Patent Information
- Application Number
- CN202411256139.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-10
AI Technical Summary
The existing 2e-redox reaction (ORR) catalysts have problems with poor stability and reaction activity in electrocatalyzed oxidation and reduction of hydrogen peroxide. In addition, traditional H2O2 production methods consume high energy and produce organic waste, so high selectivity and Highly active catalysts for sustainable synthesis.
Nanocluster intermediates are used to dopant metal elements such as Fe, Mn, Cu, Co, Ni, etc., and atomic dispersed single atom catalyst is prepared by acid solution treatment and high-temperature calcination, which is used to efficiently synthesize hydrogen peroxide under alkaline conditions.
The prepared Fe-CeOx/SiO2 catalyst has high redox potential, hydrogen peroxide selectivity and Faraday efficiency. It can continuously and efficiently produce hydrogen peroxide, with stability of more than 60 hours, yield up to 308M/gcat/h, and selectivity up to 91%. .
Smart Images

Figure CN119287422A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to an atomically dispersed single-atom catalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen peroxide (H2O2) is widely used in industries such as papermaking, pulping, disinfection, wastewater treatment, and chemical synthesis. It is one of the most important and basic chemicals. The current industrial method for large-scale production of H2O2 is the anthraquinone cycle method - using 2-alkyl and 10-anthraquinone to hydrogenate with H2 and oxidize with O2 in an organic solvent. However, this traditional production method consumes a lot of energy and produces organic waste. There are also many risks in the process of transportation and use. Therefore, it is necessary to find new H2O2 synthesis strategies to reduce energy consumption, production costs and safety issues. Electrochemistry 2e - The synthesis of H2O2 by redox reaction (ORR) has been a hot topic in recent years. Compared with traditional synthesis methods, this synthesis process can be carried out at room temperature and pressure, without the emission of organic waste such as CO2, and is a highly efficient green synthesis method. - —ORR is reduced to H2O, inhibiting the generation of H2O2. Therefore, the development of highly selective and active 2e - —ORR catalysts are an effective strategy to achieve sustainable synthesis.
[0003] The selectivity of ORR electrocatalysts is closely related to controlling the absorption intensity and electronic structure of the reaction intermediates at the active site. In order to selectively generate H2O2, the catalyst needs to absorb the reaction intermediate OOH* with the optimal binding energy to reduce it to H2O2, while retaining the OO bond to inhibit its further reduction or dissociation to O* and OH* to generate H2O. The electronic structure of single-atom catalysts can be adjusted through the central metal, coordination environment or surrounding matrix to optimize their catalytic performance in different electrochemical systems. - —ORR catalysts have been widely studied, and regulating their electronic structure to improve electrocatalytic performance is still the current research direction. At the same time, how to improve the stability of single-atom catalysts is also one of the problems that need to be solved urgently.
[0004] In recent years, atomically dispersed catalysts that “move without aggregation” have been proposed. They use nanoclusters to isolate active metal atoms, allowing them to move within the clusters but not to migrate across them, thus achieving dynamic confinement design of single atoms and breaking through the contradiction between the activity and stability of traditional catalysts. For example, the Pt-loaded single-atom catalyst prepared by Zeng et al. can withstand air calcination at up to 600 degrees Celsius. After activation, the catalyst has an activity increase of two orders of magnitude in catalyzing carbon monoxide oxidation reactions and has high stability. At present, atomically dispersed catalysts have been widely used in fields such as carbon dioxide reduction, fuel cells, and zinc-air batteries, but there is still a gap in the electrocatalytic redox production of hydrogen peroxide. Therefore, it is urgent to design a series of atomically dispersed catalysts to achieve the optimal OOH* adsorption configuration during the electrocatalytic ORR process and improve stability. Summary of the invention
[0005] In view of the deficiencies of the prior art, an object of the present invention is to provide an atomically dispersed single atom catalyst.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned atomically dispersed single-atom catalyst.
[0007] Another object of the present invention is to provide the above-mentioned atomically dispersed single-atom catalyst at 2e - —Application of ORR in the synthesis of hydrogen peroxide to solve the current 2e - —The problem of poor stability and reactivity of ORR catalysts.
[0008] The purpose of the present invention is achieved through the following technical solutions.
[0009] An atomically dispersed single-atom catalyst comprises: a nanocluster intermediate and a metal element doped on the nanocluster intermediate, wherein the metal element is one or more of Fe, Mn, Cu, Co and Ni, and the ratio of the mass fraction of the nanocluster intermediate to the molar fraction of the metal element is (50-100):1, the unit of the mass fraction is mg, and the unit of the molar fraction is μmol.
[0010] A method for preparing an atomically dispersed single-atom catalyst comprises the following steps:
[0011] Step 1, mixing the nanocluster intermediate and water until uniform, adjusting the pH value to ≤3 with an acidic solution to obtain a nanocluster intermediate solution, mixing the metal solution and the nanocluster intermediate solution under stirring conditions, stirring for at least 10 hours until uniform, filtering to obtain a yellow powder, washing, and drying to obtain a first powder, wherein the metal solution contains a metal element, and the ratio of the mass fraction of the nanocluster intermediate to the molar fraction of the metal element in the metal solution is (50-100): 1, the unit of the mass fraction is mg, the unit of the molar fraction is μmol, and the metal element in the metal solution is one or more of Fe, Mn, Cu, Co and Ni;
[0012] In step 1, the ratio of the mass fraction of the nanocluster intermediate to the volume fraction of water is (50-100):70, the unit of the mass fraction is mg, and the unit of the volume fraction is mL.
[0013] In step 1, the nanocluster intermediate and water are mixed and sonicated until homogeneous.
[0014] In step 1, an acidic solution is used to adjust the pH value to 2.7-3.
[0015] In step 1, the acidic solution is hydrochloric acid.
[0016] In step 1, the metal solution is a mixture of a metal source and a first liquid, the ratio of the amount of the metal source to the volume of the first liquid is (0.5-1.5):50, the unit of the amount of the substance is μmol, the unit of the volume is mL, the first liquid is a mixture of water and acid, and the pH of the first liquid is 2.7-3.
[0017] In the above technical solution, the metal source is one or a mixture of ferric chloride, manganese chloride, copper chloride, cobalt chloride and nickel chloride.
[0018] In step 1, the stirring speed is 800-1000 rpm.
[0019] In step 1, the method for obtaining the nanocluster intermediate is: mixing silicon dioxide and water, ultrasonicating until uniform, obtaining a first mixture, mixing cerium nitrate hexahydrate and the first mixture under stirring conditions, adjusting the pH value to 8.5-8.7, obtaining a first solution, filtering, drying, obtaining a second powder, calcining the second powder at 600-650° C. for 10-12 hours, obtaining a nanocluster intermediate, wherein the ratio of cerium nitrate hexahydrate to silicon dioxide is (100-200):360 by mass.
[0020] In the method for obtaining the nanocluster intermediate, the stirring speed is 800-1000 rpm.
[0021] In the method for obtaining the nanocluster intermediate, the ratio of the mass fraction of silicon dioxide to the volume fraction of water is (300-400):100, the unit of the mass fraction is mg, and the unit of the volume fraction is mL.
[0022] In the method for obtaining the nanocluster intermediate, the pH value is adjusted to 8.5-8.7 by using ammonia water, and the concentration of ammonia water is 2-4M.
[0023] Step 2: calcining the first powder at 600-650° C. for 10-12 hours to obtain an atomically dispersed single-atom catalyst.
[0024] In step 2, the rate of heating to 600-650° C. is 4-6° C. / min.
[0025] The above atomically dispersed single-atom catalyst is 2e - —Application in ORR synthesis of hydrogen peroxide. In the above technical solution, the atomically dispersed single atom catalyst synthesizes hydrogen peroxide under alkaline conditions.
[0026] In the above technical solution, the hydrogen peroxide production of the atomically dispersed single-atom catalyst is as high as 308M / g cat / h.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] 1. Fe-CeO prepared by the present invention x / SiO2 has a higher redox potential, with an onset potential of 0.78Vvs.RHE.
[0029] 2. Fe-CeO prepared by the present invention x / SiO2 electron transfer number is 2.2, which prefers to reduce O2 to H2O2 through a two-electron pathway, and the hydrogen peroxide selectivity is as high as 91%.
[0030] 3. Fe-CeO prepared by the present invention x / SiO2 produces up to 308M / g of hydrogen peroxide in H-type electrolytic cell cat / h, and has an ultra-high Faraday efficiency (93%).
[0031] 4. Fe-CeO prepared by the present invention x / SiO2 has high stability and can be used continuously for more than 60 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The LSV curve of the first working electrode prepared from the atomically dispersed single-atom catalysts of Examples 1 to 5 and the catalysts of Examples 6 to 7;
[0033] Figure 2 The Tafel curve of the first working electrode prepared from the atomically dispersed single-atom catalysts of Examples 1 to 5 and the catalysts of Examples 6 to 7;
[0034] Figure 3 RRDE curves of the second working electrode prepared from the atomically dispersed single-atom catalysts of Examples 1 to 5 and the catalysts of Examples 6 to 7;
[0035] Figure 4 is the electron transfer number of the second working electrode prepared from the atomically dispersed single atom catalysts of Examples 1 to 5 and the catalysts of Examples 6 to 7;
[0036] Figure 5 The hydrogen peroxide selectivity of the second working electrode prepared from the atomically dispersed single atom catalysts of Examples 1 to 5 and the catalysts of Examples 6 to 7;
[0037] Figure 6 The hydrogen peroxide production at 0.35 V vs. RHE of the first working electrode prepared from the atomically dispersed single atom catalysts of Examples 1 to 5 and the catalysts of Examples 6 to 7;
[0038] Figure 7 The hydrogen peroxide production at different voltages of the first working electrode prepared by the atomically dispersed single-atom catalyst of Example 1;
[0039] Figure 8 The Faraday efficiency of the first working electrode prepared from the atomically dispersed single-atom catalyst of Example 1 at different voltages;
[0040] Fig. 9 The third working electrode prepared from the atomically dispersed single-atom catalyst of Example 1 was subjected to a current density of 50 mA / cm 2 Stability test when
[0041] Fig.10 XRD patterns of the atomically dispersed single-atom catalyst prepared in Example 1 and the catalysts of Examples 6 to 7. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0043] The purity and purchasing manufacturers of the drugs involved in the following examples are as follows:
[0044]
[0045]
[0046] The models and manufacturers of the instruments involved in the following embodiments are as follows:
[0047] Model / Specification Instruments / Equipment Manufacturer CJB-S140 Magnetic stirrer Tianjin Kono Instrument Equipment Co., Ltd. PHS-2F Radian pH Meter Shanghai Precision Scientific Instrument Co., Ltd. 101-3A Electric constant temperature drying oven Shanghai Shengke Instrument Equipment Co., Ltd. TG16-WS Desktop high speed centrifuge Hunan Xiangyi Centrifuge Company 150ml Beaker Zhengzhou Xinyuan Glass Instrument Max2200PC X-ray diffractometer nihon rigaku co., ltd. JEM-2100F Transmission electron microscopy JEOL Ltd. U-3900H UV-Vis Spectrophotometer Hitachi Corporation CHI660E Electrochemical workstation Shanghai Chenhua Instrument Co., Ltd. AF01WV10 Rotating disk electrode device American Chemical Industry Co. CXFC-PK10 Gas Diffusion Electrode Device Shanghai Chuxi Industrial Co., Ltd.
[0048] Potassium hydroxide is a typical inorganic base. When potassium hydroxide is used as an alkaline electrolyte, oxygen can quickly generate H2O2 by reacting with water and electrons. The required potential is only 0.06V vs. RHE, which is much lower than the potential required to generate H2O2 in an acidic electrolyte (0.69V vs. RHE). Therefore, testing the production of hydrogen peroxide under the condition of potassium hydroxide as an alkaline electrolyte can prove the redox ability of the atomically dispersed single-atom catalyst.
[0049] The electrolyte in the following embodiments is a potassium hydroxide aqueous solution, and the concentration of KOH in the potassium hydroxide aqueous solution is 0.1M.
[0050] In the following examples, water is deionized water.
[0051] The cathode chamber and anode chamber of the H-type electrolytic cell in the following examples were separated by a proton exchange membrane, 10 mL of electrolyte was added to each of the cathode chamber and the anode chamber, and oxygen was introduced into the cathode chamber in advance until the chamber was saturated with oxygen.
[0052] Embodiments 1 to 5
[0053] A method for preparing an atomically dispersed single-atom catalyst comprises the following steps:
[0054] Step 1, mixing the nanocluster intermediate and water, ultrasonicating for 3 minutes until uniform, adjusting the pH value to 3 with an acidic solution (the acidic solution is hydrochloric acid, and the concentration of hydrochloric acid is 1M) to avoid the formation of hydroxide precipitation, and obtaining a nanocluster intermediate solution, slowly adding the metal solution to the nanocluster intermediate solution under stirring conditions, stirring for 10 hours until uniform, vacuum filtering, obtaining a yellow powder, washing with deionized water 3 times, and drying at 60°C for 12 hours to obtain a first powder, wherein the metal solution contains metal elements, and the mass fraction of the nanocluster intermediate and the amount of the metal element in the metal solution The ratio of the mass fraction is 50:1, and the unit of the mass fraction is m g, the unit of the amount of substance is μmol, the ratio of the mass fraction of the nanocluster intermediate to the volume fraction of water is 50:70, the unit of the mass fraction is mg, the unit of the volume fraction is mL, the metal solution is a mixture of a metal source and a first liquid (the first liquid is a mixture of water and 0.1M hydrochloric acid, and the pH of the first liquid is 3, which is used to prevent the metal solution from precipitating), the ratio of the amount of substance of the metal source to the volume fraction of the first liquid is 1:50, the unit of the amount of substance is μmol, the unit of the volume fraction is mL, the metal source is Y (the metal element in the metal solution is X), and the stirring speed is 800 rpm; X and Y are shown in Table 1.
[0055] Step 2: placing the first powder in a muffle furnace, heating the temperature to 600° C. at a heating rate of 5° C. / min and calcining at 600° C. for 12 h to obtain an atomically dispersed single-atom catalyst.
[0056] The method for obtaining a nanocluster intermediate is as follows: silicon dioxide (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) and water are mixed, ultrasonicated for 3 minutes until uniform, to obtain a first mixture, under stirring conditions, cerium nitrate hexahydrate is added to the first mixture, ammonia water (the concentration of ammonia water is 2M) is added to make the pH value 8.7, stirred for 3 minutes until uniform, to obtain a first solution, vacuum filtered, dried at 60°C for 12 hours, to obtain a second powder, the second powder is placed in a muffle furnace, heated to 600°C at a heating rate of 5°C / min and calcined at 600°C for 12 hours to obtain a nanocluster intermediate, in terms of mass fractions, the ratio of cerium nitrate hexahydrate to silicon dioxide is 167:360, the stirring speed is 800rpm, the ratio of the mass fraction of silicon dioxide to the volume fraction of water (for mixing with silicon dioxide) is 360:100, the unit of mass fraction is mg, and the unit of volume fraction is mL.
[0057] Table 1
[0058] Example X Y serial number Example 1 Fe Ferric chloride <![CDATA[Fe-CeO x / SiO2]]> Example 2 Mn Manganese chloride <![CDATA[Mn-CeO x / SiO2]]> Example 3 Cu Cupric chloride <![CDATA[Cu-CeO x / SiO2]]> Example 4 Co Cobalt chloride <![CDATA[Co-CeO x / SiO2]]> Example 5 Ni Nickel chloride <![CDATA[Ni-CeO x / SiO2]]>
[0059] Example 6
[0060] A catalyst, which is the nanocluster intermediate in embodiment 1.
[0061] Example 7
[0062] A catalyst, which is commercial SiO2 (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) with a specific surface area of 200cm 2 / g.
[0063] Redox test: At room temperature, a three-electrode system was used in an H-type electrolytic cell to perform a redox test. The three electrodes are a first working electrode, a counter electrode and a reference electrode, the counter electrode is a platinum electrode, the reference electrode is a saturated silver chloride electrode, the first working electrode is a carbon felt loaded with a catalyst, the first working electrode and the reference electrode are placed in the cathode chamber, the counter electrode is placed in the anode chamber, the LSV curve of the catalyst is measured by an electrochemical workstation, and the Tafel slope is calculated from the LSV curve. The preparation method of the first working electrode is: 50μl nafion solution is mixed with 300μl ethanol and 1mg catalyst (powder) is added, ultrasonicated for 30min to obtain a uniform first mixed solution, and then 350μL of the first mixed solution is completely applied to the surface of 1cm*1cm carbon felt, dried at 60℃ for 30min to obtain the first working electrode, and the catalyst is one of the atomically dispersed single-atom catalysts prepared in Examples 1 to 5 and the catalysts in Examples 6 to 7.
[0064] The results of the redox test are as follows Figure 1 The LSV curve and Figure 2 The Tafel curve is shown. Figure 1 As shown in Figure 1, by comparing Examples 1 to 7, it is found that the current density of the first working electrode prepared based on Example 1 is much greater than that of Examples 6 and 7 (by comparing the absolute value of the ordinate), indicating that doping metal single atoms on the nanocluster intermediate is beneficial to improving the electron transfer ability of the catalyst. 2 When the first working electrode prepared in Example 1 has a starting potential of 0.78 V vs. RHE, which is higher than that of other examples. Therefore, compared with other transition metals, Fe atom doping has the highest oxygen reduction electrocatalytic activity.
[0065] Table 2
[0066]
[0067]
[0068] Through Figure 1 The LSV curve in the figure is fitted and calculated to obtain the Tafel slope corresponding to the first working electrode prepared by the atomically dispersed single-atom catalysts of Examples 1 to 5 and the catalysts of Examples 6 to 7. The results are as follows: Figure 2 As shown in Table 3. The Tafel slope of the first working electrode prepared in Example 1 is 103 mV / dec, which is much lower than that of Examples 2 to 7, indicating that the atomically dispersed single-atom catalyst prepared in Example 1 has a higher initial electron transfer efficiency and a larger active surface in the catalytic process.
[0069] Table 3
[0070]
[0071] Figure 3 The RRDE curves of the second working electrode prepared by the atomically dispersed single-atom catalysts of Examples 1 to 5 and the catalysts of Examples 6 to 7 are shown. The RRDE curves are measured by a rotating disk electrode device, which includes: a reference electrode, a counter electrode and a second working electrode, the second working electrode is a ring disk electrode (the ring disk electrode includes a disk electrode and a platinum ring electrode), the reference electrode is a saturated silver chloride electrode, and the counter electrode is a carbon rod. The disk electrode of the second working electrode is loaded with a catalyst, and the loading method is: 50 μl of nafion solution is mixed with 950 μl of ethanol and 1 mg of catalyst (powder) is added, and ultrasonication is performed for 30 minutes to obtain a uniform second mixed solution, and then 20 μl of the second mixed solution is applied to the surface of a disk electrode with a diameter of 5.61 mm, and dried at 60° C. for 30 minutes to obtain a second working electrode, and the catalyst is one of the atomically dispersed single-atom catalysts prepared in Examples 1 to 5 and the catalysts in Examples 6 to 7. The RRDE curve measurement method is: the rotation speed and scanning speed of the disk electrode are set to 1600rpm and 10mV / s respectively, and the platinum ring electrode is kept at 1.2V vs. RHE. Under this condition, the generated hydrogen peroxide can be detected according to the disk current density of the disk electrode and the ring current density of the platinum ring electrode. The RRDE curve is shown in Figure 3 As shown. The electron transfer number (n) and hydrogen peroxide selectivity (H2O2%) are calculated based on the disk current density and ring current density in the RRDE curve. The calculation formulas for the electron transfer number (n) and hydrogen peroxide selectivity (H2O2%) are:
[0072] n=4I d / (I d +I r / N);
[0073] H2O2%=200*(I r / N) / I d +I r / N);
[0074] Among them, I d is the disk current density, I r is the ring current density, N is the current collection efficiency of the platinum ring electrode, and N is 0.36.
[0075] The electron transfer number of the second working electrode prepared by the atomically dispersed single atom catalyst of Examples 1 to 5 and the catalyst of Examples 6 to 7 at 0.3 to 0.6 V vs. RHE is as follows: Figure 4 The hydrogen peroxide selectivity of the second working electrode prepared by the atomically dispersed single atom catalysts of Examples 1 to 5 and the catalysts of Examples 6 to 7 at 0.3 to 0.6 V vs. RHE is shown as follows: Figure 5 shown.
[0076] like Figure 4 As shown, in the range of 0.3-0.6 V vs. RHE, the electron transfer numbers of Example 6 and Example 7 are approximately 3 and 3.2, respectively, and it is difficult for the electrocatalytic system to produce 2e - —ORR. The electron transfer numbers of Examples 1 to 5 are approximately 2.2, 2.76, 2.6, 2.5, and 2.35, respectively, indicating that doping with Fe single atoms is more conducive to the occurrence of 2e - —ORR. At the same time, Figure 5 As shown in Figure 2, the maximum selectivity of hydrogen peroxide in Example 1 is 91% in the range of 0.3-0.6 V vs. RHE, which further illustrates that Fe doping can improve the 2e — ORR performance, promoting the generation of hydrogen peroxide.
[0077] The production of hydrogen peroxide was determined by ultraviolet spectrophotometer-cerium sulfate colorimetric method. The determination method was as follows: 4.24 mg, 8.48 mg, 12.72 mg, 16.96 mg, and 21.2 mg of cerium sulfate tetrahydrate were dissolved in 100 mL of sulfuric acid with a concentration of 0.5 M H2SO4, respectively, to prepare Ce 4+ 5 parts of Ce at concentrations of 0.1M, 0.2M, 0.3M, 0.4M and 0.5M 4+ The original solution was measured by UV spectrophotometer for 5 parts of Ce 4+ The stock solution was analyzed for absorption spectrum at 319 nm, and a standard curve was generated. The first working electrodes prepared from the atomically dispersed single-atom catalysts of Examples 1 to 5 and the catalysts of Examples 6 to 7 were placed in the cathode chamber of an H-type electrolytic cell for constant voltage (voltage of 0.35 V vs. RHE) test, and reacted for 1 h. 50 μl of the electrolyte in the cathode chamber corresponding to the first working electrode prepared from the atomically dispersed single-atom catalysts of Examples 1 to 5 and the catalysts of Examples 6 to 7 after the reaction was added to 4 mL of 0.5 M Ce. 4+ The reaction solution was obtained from the original solution, and the absorption spectrum was analyzed to obtain the Ce in the reaction solution according to the standard curve. 4+ The concentration of hydrogen peroxide (H2O2) was calculated, and then the yield of hydrogen peroxide was obtained:
[0078] H2O2(mM)=4*[Ce 4+ ] before -4.05*[Ce 4+ ] after / (2*0.05);
[0079] Among them, [Ce 4+ ] before and [Ce 4+ ]after Ce 4+ Ce in stock solution 4+ Concentration (Ce 4+ Ce in stock solution 4+ The concentration is 0.5M) and Ce in the reaction solution 4+ concentration.
[0080] The hydrogen peroxide production of the first working electrode prepared by the atomically dispersed single atom catalysts of Examples 1 to 5 and the catalysts of Examples 6 to 7 at 0.35 V vs. RHE is as follows: Figure 6 Example 1 can continuously produce 188M / g at 0.35V vs. RHE cat / h hydrogen peroxide, is Example 6 (32M / g cat / h) is 5.87 times that of Example 7 (28M / g cat / h) is 6.7 times higher than that of the conventional method, which shows that metal doping can greatly increase the production of hydrogen peroxide. In addition, the production of hydrogen peroxide in Examples 2 to 5 at a voltage of 0.35 V vs. RHE is 54.5 to 130 M / g. cat / h, which is lower than that in Example 1, further indicating that Fe atom doping in transition metal is more conducive to the generation of hydrogen peroxide.
[0081] The method is basically the same as the above “Determination of hydrogen peroxide production by ultraviolet spectrophotometer-cerium sulfate colorimetric method”. The applied voltage is changed to determine the hydrogen peroxide production of the catalyst at different voltages (0.15-0.55 V vs. RHE). The hydrogen peroxide production of the first working electrode prepared by the atomically dispersed single atom catalyst in Example 1 at different voltages is as follows: Figure 7 As shown, at a voltage of 0.55 V vs. RHE, the first working electrode prepared by the atomically dispersed single-atom catalyst of Example 1 has a hydrogen peroxide production of 82 M / g in the ORR system. cat / h, with the decrease of applied voltage, the hydrogen peroxide production gradually increased, and at 0.15Vvs.RHE, the hydrogen peroxide production reached 308M / g cat / h, which has extremely high practical application value.
[0082] The Faradaic efficiency (FE) of the first working electrode prepared by the atomically dispersed single atom catalyst of Example 1 for synthesizing hydrogen peroxide at different voltages is as follows: Figure 8 As shown, its FE changes only slightly with the decrease of voltage, and at 0.15 V vs. RHE, its FE is still greater than 93%, which is close to the RRDE measurement value (the maximum hydrogen peroxide selectivity of Example 1 is 91% in the range of 0.3 to 0.6 V vs. RHE), indicating that hydrogen peroxide has high selectivity and weak decomposition, and has the potential for large-scale synthesis in practice.
[0083] In order to clarify the Fe-CeO x / SiO2's practical application potential was further explored using a three-electrode system and a gas diffusion electrode device. Oxygen was introduced into the gas diffusion electrode in the gas diffusion electrode device at a flow rate of 12 mL / min. In the gas diffusion electrode device, the three-electrode system consists of a third working electrode, namely a gas diffusion electrode, a reference electrode and a counter electrode. The counter electrode is a platinum electrode, and the reference electrode is a saturated silver chloride electrode. The preparation method of the third working electrode is as follows: 100 μl of nafion solution is mixed with 600 μl of ethanol and 2 mg of catalyst (powder) is added. Ultrasonication is performed for 30 minutes to obtain a uniform third mixed solution. Subsequently, 700 μl of the third mixed solution is completely applied to the surface of 2 cm*2 cm carbon felt, and dried at 60°C for 30 minutes to obtain a third working electrode. The catalyst is Fe-CeO prepared in Example 1. x / SiO2.Fe-CeO x / SiO2 is loaded on carbon felt, and the Fe-CeO x / The concentration of oxygen on the SiO2 surface provides a higher current density to increase the yield of hydrogen peroxide (the yield of hydrogen peroxide is increased to 3.22 mol / g / h, higher than 308 M / g cat / h).
[0084] The third working electrode was used at a current density of 50 mA / cm 2 When performing a constant current test (stability test), Fig. 9 As shown, the third working electrode prepared by the atomically dispersed single-atom catalyst of Example 1 is 50 mA / cm 2 The redox reaction can be carried out continuously at this current density, and the voltage remains unchanged within 62 hours (-1.6±0.02V vs.RHE), indicating that during this period, Fe-CeO x / SiO2 redox properties did not change, Fe-CeO x / SiO2 has strong stability.
[0085] The atomically dispersed single-atom catalyst prepared in Example 1 and the catalyst structures of Examples 6 to 7 were characterized using an X'Pert PRO MPD X-ray diffractometer (XRD). Fig.10 As shown, the fitting comparison shows that Fe-CeO x / The diffraction peaks of SiO2 and CeO2 overlap, but the peaks are weak and flat, so the atomically dispersed single-atom catalyst prepared in Example 1 has large-sized CeO2 nanoparticles, but the atomically dispersed single-atom catalyst prepared in Example 1 does not have the diffraction peaks of Fe element or oxide, indicating that Fe atoms have been successfully doped into the nanocluster intermediates.
[0086] This invention is the first to use atomically dispersed Fe single-atom catalysts to increase 2e - —ORR performance. The prepared Fe-CeO x / SiO2 has the largest redox current density and starting potential, and has good ORR activity. During the ORR process, O2 selectively passes through 2e - The transfer pathway is converted into hydrogen peroxide, which is comparable to commercial SiO2 and nanocluster intermediates (CeO x / SiO2), Fe-CeO x / SiO2 showed an increase of 5.87-6.7 times in the production of hydrogen peroxide at 0.35 V vs. RHE, with the best OOH* adsorption configuration.
[0087] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. An atomically dispersed single atom catalyst, characterized in that: include: A nanocluster intermediate and a metal element doped on the nanocluster intermediate, wherein the metal element is one or more of Fe, Mn, Cu, Co and Ni.
2. The atomically dispersed single-atom catalyst according to claim 1, characterized in that: The ratio of the mass fraction of the nanocluster intermediate to the molar fraction of the metal element is (50-100):1, the unit of the mass fraction is mg, and the unit of the molar fraction is μmol.
3. The method for preparing the atomically dispersed single-atom catalyst according to claim 1 or 2, characterized in that: The following steps are involved: Step 1, mixing the nanocluster intermediate and water until uniform, adjusting the pH value to ≤3 with an acidic solution to obtain a nanocluster intermediate solution, mixing the metal solution and the nanocluster intermediate solution under stirring conditions, stirring for at least 10 hours until uniform, filtering to obtain a yellow powder, washing, and drying to obtain a first powder, wherein the metal solution contains a metal element, and the ratio of the mass fraction of the nanocluster intermediate to the molar fraction of the metal element in the metal solution is (50-100): 1, the unit of the mass fraction is mg, the unit of the molar fraction is μmol, and the metal element in the metal solution is one or more of Fe, Mn, Cu, Co and Ni; Step 2: calcining the first powder at 600-650° C. for 10-12 hours to obtain an atomically dispersed single-atom catalyst.
4. The preparation method according to claim 3, characterized in that: In step 1, the ratio of the mass fraction of the nanocluster intermediate to the volume fraction of water is (50-100):70, the unit of the mass fraction is mg, and the unit of the volume fraction is mL.
5. The preparation method according to claim 3, characterized in that: In step 1, the metal solution is a mixture of a metal source and a first liquid, the ratio of the amount of the metal source to the volume of the first liquid is (0.5-1.5):50, the unit of the amount of the substance is μmol, the unit of the volume is mL, the first liquid is a mixture of water and acid, and the pH of the first liquid is 2.7-3.
6. The preparation method according to claim 3, characterized in that: In step 1, the method for obtaining the nanocluster intermediate is: mixing silicon dioxide and water, ultrasonicating until uniform, obtaining a first mixture, mixing cerium nitrate hexahydrate and the first mixture under stirring conditions, adjusting the pH value to 8.5-8.7, obtaining a first solution, filtering, drying, obtaining a second powder, calcining the second powder at 600-650° C. for 10-12 hours, obtaining a nanocluster intermediate, wherein the ratio of cerium nitrate hexahydrate to silicon dioxide is (100-200):360 by mass.
7. The preparation method according to claim 5, characterized in that: The metal source is one or a mixture of ferric chloride, manganese chloride, copper chloride, cobalt chloride and nickel chloride.
8. The atomically dispersed single atom catalyst as claimed in claim 1 or 2 at 2e - —Application in ORR synthesis of hydrogen peroxide.
9. The use according to claim 8, characterized in that: Atomically dispersed single-atom catalysts for the synthesis of hydrogen peroxide under alkaline conditions.
10. The use according to claim 8, characterized in that: The atomically dispersed single-atom catalyst produces up to 308 M / g of hydrogen peroxide cat / h.